1988
DOI: 10.1104/pp.86.3.655
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll a Fluorescence Yield as a Monitor of Both Active CO2 and HCO3 Transport by the Cyanobacterium Synechococcus UTEX 625

Abstract: Simultaneous measurements have been made of inorganic carbon accumulation (by mass spectrometry) and chlorophyll a fluorescence yield of the cyanobacterium Synechococcus UTEX 625. The accumulation of inorganic carbon by the cells was accompanied by a substantial quenching of chlorophyll a fluorescence. The quenching occurred even when CO2 fixation was inhibited by iodoacetamide and whether the accumulation of inorganic carbon resulted from either active CO2 or HCO3-transport. Measurement of chlorophyll a fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
63
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 14 publications
(29 reference statements)
1
63
0
Order By: Relevance
“…It is possible that the low-CO 2 -inducible system is supported by PSI activity that depends on electrons donation from PSII whereas the constitutive system is partially supported by cyclic PSI electron transport (Ogawa & Kaplan 2003). It has been shown that DIC accumulation in Synechococcus UTEX 625 dramatically increased electron flow from PSII to PSI and resulted in the quenching of chlorophyll fluorescence (Miller & Canvin 1987;Miller, Espie & Canvin 1988a, b, 1991Crotty, Tyrrell & Espie 1994). Much excitation energy will be used to transport DIC under C i limititation because the operation of CCM is dependent on the supply of photosynthetic energy.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the low-CO 2 -inducible system is supported by PSI activity that depends on electrons donation from PSII whereas the constitutive system is partially supported by cyclic PSI electron transport (Ogawa & Kaplan 2003). It has been shown that DIC accumulation in Synechococcus UTEX 625 dramatically increased electron flow from PSII to PSI and resulted in the quenching of chlorophyll fluorescence (Miller & Canvin 1987;Miller, Espie & Canvin 1988a, b, 1991Crotty, Tyrrell & Espie 1994). Much excitation energy will be used to transport DIC under C i limititation because the operation of CCM is dependent on the supply of photosynthetic energy.…”
Section: Discussionmentioning
confidence: 99%
“…The active transport of HC03-or CO2 causes quenching of Chl a fluorescence in Synechococcus UTEX 625 even when CO2 fixation is inhibited by iodoacetamide (14,16). Quenching does not occur in the presence of DCMU which suggests that the quenching is due to oxidation of the acceptor QA of PSII (14).…”
mentioning
confidence: 99%
“…Quenching does not occur in the presence of DCMU which suggests that the quenching is due to oxidation of the acceptor QA of PSII (14). In the presence ofiodoacetamide, CO2 reduction cannot be a means for oxidation of QA (14,16), but it is well established that 02 can also be reduced by noncycic electron transport (1,4,6). Addition of 02 can cause Q-quenching (qQ2) even in the absence of CO2 (7).…”
mentioning
confidence: 99%
“…Changes in Chl a fluorescence yield, which occurred as a consequence of DIC transport (15,18) were measured with a pulse modulation fluorometer described in (Fig. 1A).…”
Section: Fluorimetrymentioning
confidence: 99%